Factors and Impacts to Abandoned Housing Projects in Malaysia - Zuhairi, Siti Nur Afiqah; Zainal, Rozlin; Redzuan, Norul Rafidah; Shamsudin, Zarina; Shareh Musa, Sharifah Meryam (International Journal of Sustainable Construction Engineering and Technology, 2023)
Nowadays, the challenges in confronting the abandonment scenario in housing provision only foresee on buyer as the primary victim without looking at the real root causes through the project development initiator, property developer. The significance of the study is attained as housing abandonment today takes an endless time to be completed, though some still need to tediously resort to rehabilitation programs. This paper introduces the study on the contributing factors, and their impacts, and assesses their correlation relationship before developing a relationship framework. The study used a quantitative approach to obtain responsive feedback through distributed questionnaire, which revealing the perspective of Malaysia’s blacklisted property developers. By utilizing the relationship framework that highlights the most correlated factors and their impacts, the research findings serve as the best indicator for an effective mechanism controlled referred by authorities as well as constructional practitioner pertaining to the growing rate of housing abandonment in Malaysia.